Implementation of the Independent Curriculum at SMA Negeri 1 Kayuagung - Erifal, Erifal; Fitria, Happy; Eddy, Syaiful (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to determine and describe the implementation of learning, constraints, and solutions to overcome the obstacles in the implementation of the Independent Curriculum in learning management at SMA Negeri 1 Kayuagung. This type of research is descriptive qualitative research. Data collection tools use interviews, observation, documentation and literature review methods. Data analysis techniques use descriptive qualitative analysis techniques. The results showed that the implementation of the Independent Curriculum in the learning process at SMA Negeri 1 Kayuagung was carried out well but there are obstacles, and in this paper, we provided the solutions.